(3eLehYI QSGFds - (3MajO GdSYO GdJaJGRGfj , CMeO Hf jMji Hf eMeO Hf SYO GdOjf eSYhO Hf YeQ GdJaJGRGfj, Sja GdOjf,J (B916 (3g` s
(3ChdgG (B:s
(3GdebOeI CYde Gf GdYdhe GdeOhfI GdeUfaI hGdeYGQa GdeMQQI GdeDdaI Ydi fhYjf GdChd eGOhfg GdeJTQYI dHjGf CdaGX GdbQBf s
(3BNQgG (B:s
(3GdSQai Gf MLe GdjO Gdjefi GcHQ ef MLe GdjO GdjSQi Gf MQcI Gdjefi GcKQ ef MQcI GdjSQi fMeO Gddg JYGdi Ydi GaVGdg ai LejY GdGHhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B205s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeYGQa GdYGeIs